From miracle to mirage: the ANC`S economic policy shift from MERG to GEAR - Nkadimeng, Mphahle Geoffrey (My University, 2014)
The thesis explores the ANC’s economic policy shifts from its initial inclination towards a Keynesian model in the form of the Macroeconomic Research Group (MERG) report to that of a free-market model in the form of Growth, Employment and Redistribution (GEAR). It argues that the shifts which began earnestly in the 1990s may be explained through the conceiving of policy making as a process which involves different actors that compete with each other to influence state policy in the direction of their respective interests. In order to understand and explain the ANC’s economic policy shifts, the thesis utilises theories of transition and policy making. It argues that while both external and internal factors could be used to explain the shifts, in the South African case these factors manifest themselves in a more complex way than has been the case in other modern countries. This emphasis takes into account the fact that South African’s transition to democracy is not only confined to democratic political process but it also involves quite sophisticated forms of structural transition in which the historically disadvantaged racial groups are attaining new social status and economic strata. It is these developments which in one way or the other, contributed to a need for the ANC to accommodate new interests groups that have not historically formed part of its traditional support base.